Anxiety and associated factors in Northwest Ethiopian pregnant women: a broad public health concern - Haile, Tsion Tadesse; Kebede, Azmeraw Ambachew; Gessesse, Dereje Nibret; Tsega, Nuhamin Tesfa; Aklil, Mastewal Belayneh; Temesgan, Wubedle Zelalem; Anteneh, Tazeb Alemu; Tibebu, Nebiyu Solomon; Alemu, Haymanot Nigatu; Seyoum, Asmra Tesfahun; Tiguh, Agumas Eskezia; Yismaw, Ayenew Engida; et al. (Frontiers in Public Health, 2024)
Introduction Pregnancy-related anxiety is a prevalent mental health issue that mostly affects women in low-income countries such as Ethiopia. It has been linked to unfavorable pregnancy outcomes, such as miscarriage, prematurity, and low birth weight. However, it has often received less attention, and community-based evidence lacks its prevalence and associated factors. Thus, the purpose of this study was to assess the prevalence and associated factors of anxiety in Northwest Ethiopian pregnant women in Gondar city. Methods A community-based cross-sectional study was conducted from 1 July to 30 August 2021 in Gondar city. A cluster sampling technique was used to select a sample of 872 pregnant women, and in-person interviews were conducted to gather data. Descriptive and analytical statistical procedures were carried out. Results Of the participants, pregnancy-related anxiety was reported in 29.4% (95% CI: 26.3, 32.4) of women. The likelihood of having anxiety was higher among women who had known medical illness (AOR = 3.16; 95% CI: 1.8, 5.35), loneliness (AOR = 2.52; 95% CI: 1.34, 4.73), depression (AOR = 2.38; 95% CI: 1.48, 3.85), poor social support (AOR = 1.93; 95% CI: 1.21, 3.07), and intimate partner violence (AOR = 2.87; 95% CI: 2.04, 4.04). Conclusion In this study, three out of ten women have suffered from anxiety. It is strongly advised to identify and treat known medical illnesses early in pregnancy, enhance social support, diagnose and treat depression, and limit intimate partner violence through multimodal and integrative activities with concerned bodies.